Numerical Simulation of the Effect of Variation in Subgrade CBR Values on Rigid Pavement - Suprapto Siswosukarto; M Muslikh; Taufiq Adi Wijoyo (JACEE (Journal of Advanced Civil and Environmental Engineering), 2023)
This study presents the results of research on the stress behavior of rigid pavement concrete slabs by varying CBR subgrade values. It aims to know the effect of changing the rigid pavement strss. Data used in this study are geometric data and material properties of the pavement structure. The load vehicle considered is National Road class standard. Rigid pavement is very sensitive with un-uniformity of underlaying supposrt. In this research, the effect of un-uniform support of subgrade was modeled numerically using Abaqus software. The friction coefficient of each layer was also considered in the model. Model simulation of existing rigid pavement calculated 13 variations of CBR values. Result shown that there is a stress increment by 26.27% in the longitudinal direction of the rigid pavement between models with uniform variations of CBR and models with non-uniform variations of CBR. This result show the sensitivity of rigid pavement to un-uniformity of subgrade.